2015
DOI: 10.1111/pme.12526
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pain, Functioning, Coping, and Psychological Distress in Patients with Chronic Low Back Pain Evaluated for Spinal Cord Stimulator Implant or Behavioral Pain Management

Abstract: Pre-SCS patients possibly underreport psychological symptoms perhaps to gain SCS approval for SCS. Separate norms and cutoffs for pre-SCS psychological evaluations may be needed to better identify risks of unsuccessful outcomes. Validity scales for measures of psychological distress also could be developed to detect biased reporting. Alternatively, referring clinicians may have referred patients for BPM who were more psychologically distressed and perceived as more in need of psychosocial intervention than tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Additionally, a recent study by Davis and his colleagues compared patients with chronic back pain, who were referred for either SCS or behavioral pain management (BPM), and found that patients who were referred for SCS reported similar pain and functioning scores but fewer psychological symptoms of distress compared to patients referred to BPM . They concluded that pre‐SCS patients may underreport psychological symptoms to gain approval for SCS and suggested different norms and cutoffs for pre‐SCS psychological evaluations to better identify risks of unsuccessful outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent study by Davis and his colleagues compared patients with chronic back pain, who were referred for either SCS or behavioral pain management (BPM), and found that patients who were referred for SCS reported similar pain and functioning scores but fewer psychological symptoms of distress compared to patients referred to BPM . They concluded that pre‐SCS patients may underreport psychological symptoms to gain approval for SCS and suggested different norms and cutoffs for pre‐SCS psychological evaluations to better identify risks of unsuccessful outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These factors have been found to increase risk for acute low back pain developing into chronic pain, and for increased risk of disability associated with low back pain [ 7 , 8 , 9 ]. In addition, these factors adversely impact outcomes of both surgical intervention as well as success of interventional technologies such as spinal cord stimulation or intrathecal pumps for pain control [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, also of interest is whether preoperative optimization of such psychological comorbidity affects patients' decision to proceed with SCS following the trial and the overall pain and disability outcome of such therapy. A caveat recently reported by Davis and coworkers (41) is that pre-SCS patients report similar pain but lesser degree of psychological distress than patients for whom SCS was not offered. This retrospective work may simply reflect patient selection; however, the authors propose that pre-SCS patients may underreport psychological symptoms to be approved for this therapy.…”
Section: Discussionmentioning
confidence: 90%